Pengembangan Media KAMBURA Berbasis Scratch pada Materi Keragaman Budaya Pelajaran Pendidikan Pancasila Kelas V SD - Melda Puspita Sari; Ika Ari Pratiwi; Denni Agung Santoso (Universitas Ngudi Waluyo, 2026)
The learning process in elementary schools still faces challenges, including students’ lack of focus, susceptibility to distraction, and low learning motivation among some learners, which impact learning outcomes. This study aims to develop the KAMBURA learning media and analyze its level of validity and practicality in elementary school learning. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included expert lecturers, a teacher, and 23 fifth-grade students of SD 1 Mejobo. The instruments used were interview and observation sheets, expert validation sheets covering material, media, and language aspects, as well as practicality questionnaires completed by the teacher and students. Data were analyzed by calculating the percentage of the obtained scores and converting them into validity and practicality criteria. The results showed that the KAMBURA media was categorized as very valid, with percentages of 92% from the material expert, 94% from the media expert, and 91% from the language expert. The practicality test indicated that the media was classified as very practical, with a percentage of 90% from the teacher and 93% from the students. Therefore, the KAMBURA media is feasible and practical for use in elementary school learning. The implications of this study indicate that KAMBURA can serve as a reference for teachers in developing interactive learning media based on Scratch. Abstrak Proses pembelajaran di sekolah dasar masih menghadapi permasalahan berupa kurangnya fokus, mudah terdistraksi, serta rendahnya motivasi belajar sebagian siswa yang berdampak pada hasil belajar. Penelitian ini bertujuan untuk mengembangkan media KAMBURA serta menganalisis tingkat kevalidan dan kepraktisannya dalam pembelajaran di sekolah dasar. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Subjek penelitian terdiri atas dosen ahli, guru, dan 23 siswa kelas V SD 1 Mejobo. Instrumen yang digunakan meliputi lembar wawancara, observasi, validasi ahli materi, ahli media, dan ahli bahasa, serta angket kepraktisan oleh guru dan siswa. Data dianalisis dengan menghitung persentase skor dan mengonversikannya ke dalam kriteria kevalidan dan kepraktisan. Hasil penelitian menunjukkan bahwa media KAMBURA termasuk kategori sangat valid dengan persentase 92% oleh ahli materi, 94% oleh ahli media, dan 91% oleh ahli bahasa. Uji kepraktisan menunjukkan kategori sangat praktis dengan persentase 90% oleh guru dan 93% oleh siswa. Dengan demikian, media KAMBURA layak dan praktis digunakan dalam pembelajaran sekolah dasar. Implikasi penelitian ini menunjukkan bahwa media KAMBURA dapat dijadikan referensi bagi guru dalam pengembangan media pembelajaran interaktif berbasis scratch.